The effects of creatine supplementation on upper- and lower-body strength and power: a systematic review and meta-analysis - Kazeminasab, F.; Bahrami Kerchi, A.; Sharafifard, F.; Zarreh, M.; Forbes, S. C.; Camera, D. M.; Lanhers, C.; Wong, A.; Nordvall, M.; Bagheri, R.; Dutheil, F. (Nutrients, 2025)
Background: Creatine supplementation is widely used to enhance exercise performance, mainly resistance training adaptations, yet its differential effects on upper- and lower-body strength and muscular power remain unclear across populations. Objective: This systematic review and meta-analysis aimed to quantify the effects of creatine supplementation in studies that included different exercise modalities or no exercise on upper- and lower-body muscular strength and power in adults.